2021
DOI: 10.1098/rspb.2021.0765
|View full text |Cite
|
Sign up to set email alerts
|

Limited plasticity in thermally tolerant ectotherm populations: evidence for a trade-off

Abstract: Many species face extinction risks owing to climate change, and there is an urgent need to identify which species' populations will be most vulnerable. Plasticity in heat tolerance, which includes acclimation or hardening, occurs when prior exposure to a warmer temperature changes an organism's upper thermal limit. The capacity for thermal acclimation could provide protection against warming, but prior work has found few generalizable patterns to explain variation in this trait. Here, we report the results of,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 110 publications
(126 reference statements)
5
52
0
Order By: Relevance
“…In another study, Barley et al conducted a metaanalysis of within-species variation in thermal plasticity, but did not find support for the climate variability hypothesis [18]. Instead, their analysis showed that populations with greater thermal tolerance had reduced plasticity, which was evidence for trade-offs between thermal tolerance and thermal plasticity [18].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Barley et al conducted a metaanalysis of within-species variation in thermal plasticity, but did not find support for the climate variability hypothesis [18]. Instead, their analysis showed that populations with greater thermal tolerance had reduced plasticity, which was evidence for trade-offs between thermal tolerance and thermal plasticity [18].…”
mentioning
confidence: 99%
“…Two studies in this Special Feature challenge the widespread notion that increased climate variability also increases thermal tolerance and plasticity [18,19]. Bitter et al reviewed theoretical predictions for the evolution of plasticity in fluctuating environments, and showed that it is the predictability (rather than the amplitude) of fluctuations that primarily drive the amount of phenotypic plasticity present in natural populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from natural study systems is required to clarify under which conditions plasticity is favored or hindered by evolution. A meta-study by Barley et al (2021) quantified thermal acclimation capacity across 19 species including arthropods, molluscs, and chordates, showing that within species, marginal populations experiencing the highest thermal conditions had decreased plasticity and acclimation capacity. A negative relationship between plasticity and adaptation to heat extremes was also found in laboratory experiments (Kelly et al, 2017;Sasaki & Dam, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by current debate surrounding the Trade-off Hypothesis and increasing interest in the evolution of phenotypic plasticity and genetic assimilation under global change (Gunderson and Stillman 2015; Kelly 2019; Sasaki and Dam 2019; van Heerwaarden and Kellermann 2020; Barley et al 2021; Preston et al 2021; Sasaki and Dam 2021), we used simulations to explore the more general consequences of regression to the mean for tests of genetic assimilation at the macroevolutionary level. We conducted simulations that assumed mechanistically different models for plasticity evolution, as well as different experimental sampling designs for measuring species phenotypic traits.…”
Section: Introductionmentioning
confidence: 99%